Microbiology and antimicrobial susceptibility of otitis externa: a changing pattern of antimicrobial resistance. Issue 4 (12th February 2018) - Heward, E; Cullen, M; Hobson, J
Abstract: Objective: Otitis externa is a common presentation to secondary care otolaryngology clinics. Despite this, few studies have investigated the microbiology and antimicrobial resistance of otitis externa. This study aimed to examine these issues. Methods: Analysis identified 302 swabs taken from 217 patients (100 male, 117 female), between 1 January 2015 and 30 March 2016, at our rapid access otolaryngology clinic. Results: In total, 315 organisms were isolated; the most frequent was Pseudomonas aeruginosa (31.1 per cent), followed by candida species (22.9 per cent) and Staphylococcus aureus (11.7 per cent). P aeruginosa was sensitive to ciprofloxacin in 97.7 per cent of cases and to gentamicin in 78.4 per cent. Conclusion: Compared with studies worldwide, the relative proportions of different organisms causing otitis externa and the patterns of antimicrobial resistance differ. Increasing resistance of P aeruginosa to aminoglycosides demonstrates a changing pattern of antimicrobial resistance that has not been previously reported. Reassuringly, quinolone antibiotics remain highly effective when treating P aeruginosa .